Category specificity in early perception: face and word N170 responses differ in both lateralization and habituation properties - Maurer, Urs; Rossion, Bruno; McCandliss, Bruce D. (Frontiers in Human Neuroscience, 2008)
N170 event-related potential (ERP) responses to both faces and visual words raises questions about category specific processing mechanisms during early perception and their neural basis. Topographic differences across word and face N170s suggests a form of category specific processing in early perception – the word N170 is consistently left-lateralized, while less consistent evidence supports a right-lateralization for the face N170. Additionally, the face N170 shows a reduction in amplitude across consecutive individual faces, a form of habituation that might differ across studies thereby helping to explain inconsistencies in lateralization. This effect remains unexplored for visual words. The current study directly contrasts N170 responses to words and faces within the same subjects, examining both category-level habituation and lateralization effects. ERP responses to a series of different faces and words were collected under two contexts: blocks that alternated faces and words vs. pure blocks of a single category designed to induce category-level habituation. Global and occipito-temporal measures of N170 amplitude demonstrated an interaction between category (words, faces) and block context (alternating categories, same category). N170 amplitude demonstrated class-level habituation for faces but not words. Furthermore, the pure block context diminished the right-lateralization of the face N170, pointing to class-level habituation as a factor that might drive inconsistencies in findings of right-lateralization across different paradigms. No analogous effect for the word N170 was found, suggesting category specificity for this form of habituation. Taken together, topographic and habituation effects suggest distinct forms of perceptual processing drive the face N170 and the visual word form N170.